Beta Blocker Therapy for Congenital Hepatic Arteriovenous Fistula in Two Neonates - Ba, Hongjun; Xu, Lingling; Peng, Huimin; Lin, Yuese; Li, Xuandi; Qin, Youzhen; Wang, Huishen (Frontiers in Pediatrics, 2020)
Introduction: Hepatic arteriovenous fistula (HAVF) is an abnormal communication between the hepatic arteries and hepatic veins. This condition is treated mainly using interventional closure and surgery. However, these procedures are associated with many postoperative complications and high mortality. Propranolol and other beta blockers have been used widely and effectively to treat infantile hemangiomas. However, no reports describe the use of these drugs to treat congenital HAVF. Case Description:Here, we present two cases in which beta blocker therapy was used to treat congenital HAVF in neonates. In both cases, antenatal examinations revealed cardiac enlargement and hepatic space-occupying lesions. After birth, both patients rapidly presented with respiratory distress, cyanosis, and heart failure. Echocardiography suggested enlargement of the right heart, widening of the pulmonary artery, and severe pulmonary arterial hypertension, and hepatic examinations revealed HAVF. Results:After admission, the patients were treated with dopamine, milinone, and furosemide for heart failure. However, their conditions worsened, as indicated by nod-like breathing and cyanosis. Endotracheal intubation and ventilator-assisted breathing and a small dose of oral propranolol (1 mg/kg/d) were initiated. The patients' conditions improved, as indicated by decreases in levels of the N-terminal pro-hormone BNP, and the ventilators were removed. The propranolol dose was increased gradually to 2 mg/kg/d. After 2 weeks of propranolol treatment, the neonate in case 2 developed bronchospasm, which improved after propranolol treatment ended and metoprolol treatment was initiated. Liver imaging performed 8–9 months after beta blocker therapy suggested the disappearance of the arteriovenous fistulae in case 2, and close to disappearing of the arteriovenous fistulae in case 1. Conclusion:Propranolol and metoprolol can effectively treat HAVF in infants, an observation consistent with that found in earlier studies that have shown beta blockers are a valid medical treatment option for infantile hemangioma. However, future studies should explore the underlying potential mechanism.